Ultrasound-assisted chitosan-surfactant nanostructure assemblies: towards maintaining postharvest quality of tomatoes - Mustafa, Maysoun A. (Springer Verlag, 2014)
A novel ultrasound-assisted chitosan–surfactant nanostructure assembly was developed to allow better delivery of chitosan particles into intact fruit tissues for extension of postharvest life. Three solutions of 1 % chitosan–surfactant nanostructure assembly with micelle sizes of 400, 600 and 800 nm were prepared and applied as an edible coating on tomatoes. The fruits were stored at 15 ± 2 °C and 70–80 % relative humidity for 20 days. The indicators of tomato ripening, which included loss of firmness, decline of titratable acidity, decline of chlorophyll content and increase in soluble solid content, were delayed in the treated fruits in comparison to the control (p < 0.05). A delay of approximately 5 days in ripening was observed by evaluating the colour evolution from green to red. The treatment significantly (p < 0.05) enhanced the phenolic content while maintaining a lower level of respiration in comparison to the control, throughout most of the storage duration. However, weight loss was higher in the treated fruits in comparison to the control. No significant difference in the resultant effects was observed by using chitosan–surfactant nanostructure assemblies of different micelle sizes (p > 0.05).